Gaya Komunikasi Antara Orang Tua dan Anak dalam Upaya Menciptakan Sikap Positif dalam Belajar - Earth Yakhin Da’boas Abedneju Lasut; Iin Soraya; Cindya Yunita Pratiwi (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Communication Styles Between Parents and Children in an Effort to Create a Positive Attitude in Learning". This study examines how communication styles between parents and children shape positive learning attitudes in Kumersot Village, North Sulawesi. Using qualitative methods with a case study approach, the research identifies that assertive and democratic communication enhances children's confidence, learning interest, and independence. In contrast, aggressive and non-assertive communication causes emotional tension and reduces motivation. The study also highlights technology and social media as challenges to effective communication. It recommends adopting open and supportive communication to foster a positive learning environment.